Determinants of gluten-free diet adoption among individuals without celiac disease or non-celiac gluten sensitivity. (1st January 2021) - Arslain, Kristina; Gustafson, Christopher R.; Baishya, Pratiksha; Rose, Devin J.
Abstract: Objectives: Gluten-free (GF) foods are typically less nutritious and more expensive than their gluten-containing variants, yet people without a diagnosed gluten sensitivity continue to adopt this diet. There is a lack of research about what factors drive people without Celiac disease or non-Celiac gluten sensitivity to follow the GF diet. Methods: A nationally representative sample of 2982 US residents without a diagnosed gluten sensitivity were surveyed about their attitudes, perceptions, and experiences with the GF diet. Logistic regression was used to compare respondents who were currently avoiding or had avoided gluten previously (GF consumer) to respondents who had never tried a GF diet (non-GF consumer). Results: Over one-fifth of respondents were GF consumers. Beliefs that a gluten-reduced diet is healthier (OR 1.69; 95% CI [1.30, 2.18]), that GF products are more nutritious (OR 1.46, 95% CI [1.11, 1.90), and that a GF diet can help clear acne (OR 1.46; 95% CI [1.13, 1.88]) were all positively associated with trying a GF diet. Personal research was the most influential source of information associated with trying a GF diet (OR 2.92; 95% CI [1.91, 4.52]). This was followed by "healthcare center or health professional" (OR 2.57; 95% CI [1.71, 3.90]. Respondents who were never encouraged to try the GF diet were less likely to try the diet (OR 0.33, 95% CI [0.23, 0.46]). Conclusions: Positive, but scientifically unsubstantiated, beliefs about the benefits of the GF diet were strongly associated with trying a GF diet, and the source of recommendation to try a GF diet was important.